PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN RETURN ON INVESTMENT TERHADAP HARGA SAHAM PERUSAHAAN FOOD & BAVERAGES - ILMIYATUS SAJIYAH (Jurnal Akademika, 2016)
This study aims to identify and analyze the financial statements based on the Current Ratio(CR), Debt to Equity Ratio (DER) and Return On Investment (ROI) Share Price Food &baverages Companies Listed on the Stock Exchange in 2010-2014. Data were obtained fromthe annual financial statements and the Annual Report of the Investment Gallery STIEIndonesia Malang and Indonesia Stock Exchange (IDX) during the period 2010-2014. Thisresearch is a quantitative research. The population in this study using all companies listedon the Stock Exchange with a company specializing in food and beverages totaling 19issuers during the period 2010-2014 and the number of samples as many as six companiesthrough random sampling method.The results showed that partially shows that the Current Ratio (CR) and Debt to EquityRatio (DER) and no significant negative effect on stock price. While simultaneously variableCurrent Ratio (CR), Debt to Equity Ratio (DER) and Return On Investment (ROI) onstock prices. And the results also showed that the Return On Investment (ROI) has a positiveand significant impact on stock price of companies Food & baverages 2010-2014.Keywords: Capital Markets, the Current Ratio (CR), Debt to Equity Ratio (DER), ReturnOn Investment (ROI) and stock price.